VISUAL MODELLING AND SIMULATION INTEGRATION TOOLS - Georgy N. Khubayev; Sergey M. Scherbakov; Yury A. Rvantsov (Вестник Донского государственного технического университета, 2018)
The information system that realizes the integration concept of the visual modelling and simulation is considered.